Die fiktive Integration der Stadtstaaten im Rahmen des Länderfinanzausgleichs - Michael Broer (Wirtschaftsdienst, 2016)
Die Stadtstaatenregelung im Länderfinanzausgleich sieht vor, dass durch die Einwohnerveredelung finanzielle Mittel zu den Stadtstaaten umgeleitet werden. Nicht diese besondere Berücksichtigung, sondern das gegenwärtige Verfahren ist dabei umstritten. Der Wissenschaftliche Beirat beim Bundesministerium der Finanzen schlägt eine fiktive Integration der Stadtstaaten vor. Der Autor untersucht diesen Vorschlag empirisch. – – The German states Bavaria and Hesse have initiated a legal case against the German fiscal equalisation system. One thing which is criticised is the special treatment afforded to the so-called city-states Berlin, Bremen and Hamburg. Citizens of these states are weighted with 135% instead of the standard 100% weighting of citizen in other federal states. There are different proposals to deal with this spillover problem. One proposal by the advisory board of the Federal Ministry of Finance was for a virtual fusion of the city-states with their neighbouring states, for fi scal equalisation purposes only. This paper analyses the effects of such a virtual fusion on the fi scal equalisation system.
Keywords: H70; H77; 330; Länderfinanzausgleich; Finanzverfassung; Teilstaat; Stadt; Bevölkerungsdichte; Deutschland